Boulevard of Broken Dreams : Why Public Efforts to Boost Entrepreneurship and Venture Capital Have Failed--and What to Do about It - Lerner, Joshua (Book collections on Project MUSE., 2009)
Discussing the complex history of Silicon Valley and other pioneering centres of venture capital, Lerner uncovers the extent of government influence in prompting growth. He examines the public strategies used to advance new ventures and reveals the common flaws undermining far too many programmes.